Long-Term Cover Crop Management Effects on Soil Health in Semiarid Dryland Cropping Systems - L. M. Simon; A. K. Obour; J. D. Holman; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2020)
Growing cover crops (CC) in semiarid drylands may provide benefits to soil health. This study examined long-term CC management effects in a no-till winter wheat-grain sorghum-fallow cropping system in southwest Kansas. Objectives were to assess the impacts of CCs on 1) soil organic carbon (SOC) and nitrogen (N) stocks, 2) soil susceptibility to erosion, as well as to 3) quantify the effects of haying cover crops as annual forages. Treatments were spring-planted and included peas for grain as well as one-, three-, and six-species CC mixtures of oats, triticale, peas, buckwheat, turnips, and radishes compared with conventional chemical-fallow. Half of each CC treatment was harvested for forage. All phases of each rotation were present every year. Soil samples were collected from the 0- to 6-inch depth in 2018 and 2019 corresponding with wheat planting and harvest in the three-year rotation. Results indicate no significant difference in SOC with CCs compared to fallow in either 2018 or 2019, though SOC stocks were greater than in 2012. This was possibly due to periods of drought reducing total carbon (C) inputs compared to earlier periods of relatively greater precipitation. Haying of CCs had no effect on soil health indicators compared to when CCs were left standing. Soil N was not increased with CCs compared to fallow or peas. Mean weight diameter of wet aggregates in 2018 was not different between CCs hayed (0.042 in.) and CCs left standing (0.044 in.) but were greater than fallow (0.033 in.) or peas (0.030 in.). Growing a CC significantly increased the proportion of larger (0.30- to 0.08-in.) aggregates (37%) compared to peas (21%) but not compared to fallow (24%). These differences were not significant after wheat harvest in 2019. Our findings suggest that CCs may improve soil physical properties compared to conventional chem-fallow in semiarid dryland cropping systems.
Keywords: cover crops; dryland; soil health